Analysis of the activation mechanism of Pseudomonas stutzeri cytochrome c peroxidase through an electron transfer chain - Sousa, P. M. Paes de (2011)
J Biol Inorg Chem (2011) 16:881–888 DOI 10.1007/s00775-011-0785-8